Pengembangan Aplikasi Penentuan Prioritas Kebutuhan Perangkat Lunak Dengan Metode Value Oriented Prioritization (VOP) - Hanida Aisha; Denny Sagita Rusdianto; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The success of the software depends on the selection of needs that are prioritized properly. Priority needs are considered as one of the most important approaches in the process of needs engineering. needs prioritization is used to determine the bookings or the schedules to carry out the needs based on their priorities or interests with respect to the stakeholders' point of view. There are various techniques and methods that have been proposed by the researchers. In this study, the researcher applies the priority method proposed by Jim Azar, Randy K. Smith, and David Cordes to prioritized the software needs which only use a core business value. The Value-Oriented method Prioritization is a method that emphasizes the main business value in the process of determining the priority, using an ordinal scale according to how important the business in the company is. the risk of the business carried on by the company is also identified and given a positive value for weighting the business core, while a negative value for weighting the risk. This application has been tested for functional and non functional requirements, functional requirements using black-box testing, namely validation testing, and white box testing, namely unit testing and integration and non functional requirements using compatibility testing with the help of sortsite software with the result of not getting critical issues in many browsers and acuuracy testing, so it can be concluded that it gets a valid results.